Red Thermally Activated Delayed Fluorescence in Dibenzopyridoquinoxaline-Based Nanoaggregates - Das, Subhadeep; Kundu, Subhankar; Sk, Bahadur; Sarkar, Madhurima; Patra, Abhijit (Organic Materials, 2021)
All-organic thermally activated delayed fluorescence (TADF) materials have emerged as potential candidates for optoelectronic devices and biomedical applications. However, the development of organic TADF probes with strong emission in the longer wavelength region (> 600 nm) remains a challenge. Strong π-conjugated rigid acceptor cores substituted with multiple donor units can be a viable design strategy to obtain red TADF probes. Herein, 3,6-di-t-butyl carbazole substituted to a dibenzopyridoquinoxaline acceptor core resulted in a T-shaped donor–acceptor–donor compound, PQACz-T, exhibiting red TADF in polymer-embedded thin-films. Further, PQACz-T self-assembled to molecular nanoaggregates of diverse size and shape in THF–water mixture showing bright red emission along with delayed fluorescence even in an aqueous environment. The self-assembly and the excited-state properties of PQACz-T were compared with the nonalkylated analogue, PQCz-T. The delayed fluorescence in nanoaggregates was attributed to the high rate of reverse intersystem crossing. Moreover, an aqueous dispersion of the smaller-sized, homogeneous distribution of fluorescent nanoparticles was fabricated upon encapsulating PQACz-T in a triblock copolymer, F-127. Cytocompatible polymer-encapsulated PQACz-T nanoparticles with large Stokes shift and excellent photostability were demonstrated for the specific imaging of lipid droplets in HeLa cells.
Keywords: TADF; dibenzopyridoquinoxaline; nanoaggregates; fluorescence imaging; lipid droplets